Dalil Dalil Hukum Thalaq - Rahmadhani Simatupang; Muhammad Amar Adly; Heri Firmansyah (Jurnal Kajian dan Penelitian Umum, 2025)
This research Divorce being a way to solve conflict in the household. Then, Islam came to bring down the Qur’an as guidelines and learness for Moslem, even though some of them have problems with the language. Now, there are interpretation works from past and contemporarych will discuss about how Islam pay attention on woman side that plenty be aggrieved before Qur’an came down. It prevent the disadvantage can not happen in the divorce and know the solution that given by Surah aṭ-Ṭalāq ayat 1-7 with used Al-Mishbah interpretation in M. Quraish Shihab related to the problems that happen in society. From this research, interpretations from Quraish Shihab discuss talak laws that are described in detail from vocabulary aspect until opinion of other ulama. One of them is ‘iddah and Talak terms that are considered in menstrual and pregnant periods of a wife. According to the writer, the step that can be taken is to become more selective in choosing a husband or wife partner. Although this is known to be hard to do because of the possibility of divorce later, at least it can be a form of prevention.